The legacies of the “Father of Hybrid Rice” and the seven representative achievements of Chinese rice research: A pioneering perspective towards sustainable development - Gao, Jian-Guo; Zhu, Xin-Guang (Frontiers in Plant Science, 2023)
The “Father of Hybrid Rice”, Yuan Longping, created high-yield hybrid rice that can feed tens of millions of people annually. The research achievements of Yuan and his team on low cadmium-accumulating rice and sea rice, in addition to hybrid rice, as well as those of a large number of Chinese scientists engaged in rice research in other six areas, including the rice genome, purple endosperm rice, de novo domestication of tetraploid rice, perennial rice, rice blast disease, and key genes for high nitrogen use efficiency, play an important role in promoting the realization of the United Nations Sustainable Development Goals 2 and 12. The purpose of this review is not to elaborate on the details of each research, but to innovatively summarize the significance and inspiration of these achievements to ensure global food security and achieve sustainable agriculture. In the future, cultivating new rice varieties through modern biotechnology, such as genome editing, will not only reduce hunger, but potentially reduce human-land conflicts, improve the environment, and mitigate climate change.